What (economic) Constitution does the EU need? - Laurent, Eloi; Le Cacheux, Jacques (Paris, 2007)
"The European Constitutional Treaty (ECT) was presented by its drafters as an explicit constitution for the European Union (EU 25). A possible explanation for its rejection by the French and Dutch citizens in the course of spring 2005 is that it did not sufficiently amend the implicit constitution of the EU 25,the European Union Treaty (EUT), which was truly the object of voters’ aversion. Assuming this to be true, there should be a thorough debate on the relevance and viability of the de facto current constitution of the European Union. In this paper, we engage in this debate by identifying what is essentially wrong with the economic provisions of the EUT, which we designate as the “European economic constitution.” Using a constitutional political economy approach, we first attempt to demonstrate that both what we define as the “principle of integrity” and the “principle of efficiency” of collective action appear to be violated by the European economic constitution. This ccurs, respectively, because its provisions are not neutral, nor revisable, and ecause they do not sufficiently allow for the possibility of cooperative collective decision (leading to convergence in welfare) in a more than ever numerous and heterogeneous EU. Our essential argument in this respect regards the implications of the structurally different economic performances and incentives of small and large countries under the European economic constitution. Finally, since the present European trade-off between “integrity” and “efficiency” appears sub-optimal, we present two original ways of achieving potentially better ones in the EU, through a “Great compromise” or “Economic constitution(s),”expressing a preference for the latter."